Analisis Efisiensi dan Efektivitas Realisasi Anggaran Belanja pada Dinas Koperasi, UMK, UM dan Perindustrian Kota Metro Tahun Anggaran 2017-2020 - Drajat Armono; Nur Widiyaningsih; Nurhayanto (Program Sarjana Terapan Universitas Islam Indonesia, 2023)
Abtract The budget is an important tool in public sector organization as well as in the private sector, because the budget is used as a measuring tool or performance appraisal to be achieved in the future and is expressed in numbers. Therefore, this study aims to determine and measure the level of efficiency and effectiveness of the local government’s performance of the Departement of Cooperatives, UMK, UM and Metro City Industry in realizing the budget starting from the 2017-2020 period. This study uses the Budget Realization Report obtained from the object of research. The result of this study conclude that the calculation of the average use of the budget is quite effective and efficient. The use of the budget is said to be successful if the realization does not exceed the budgeted figure. Keywords: Budget, Efficiency, Effectiveness, Performance Measurement